2007
DOI: 10.1093/jhered/esm093
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Biallelic Markers and Microsatellites for the Estimation of Population and Conservation Genetic Parameters in Atlantic Salmon (Salmo salar)

Abstract: Biallelic markers such as single nucleotide polymorphisms (SNPs) and insertion/deletion polymorphisms have become increasingly popular markers for various population genetics applications. However, the effort required to develop biallelic markers in nonmodel organisms is still substantial. In this study, we compared the estimation of various population genetic parameters (genetic divergence and structuring, isolation-by-distance, genetic diversity) using a limited number of biallelic markers (in total 7 loci) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
59
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 59 publications
14
59
1
Order By: Relevance
“…Standardized F ST was usually several times higher than unstandardized F ST for microsatellite loci (e.g., Criscione et al 2007;Jordan and Snell 2008;González-Pérez et al 2009). Standardizing of F ST became now a required procedure when different markers are compared or combined for analysis (e.g., Langergraber et al 2007;Ryynänen et al 2007). Therefore, our study as well as other published studies confirmed a necessity of using a standardized measure of genetic differentiation when measures are based on different genetic markers.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Standardized F ST was usually several times higher than unstandardized F ST for microsatellite loci (e.g., Criscione et al 2007;Jordan and Snell 2008;González-Pérez et al 2009). Standardizing of F ST became now a required procedure when different markers are compared or combined for analysis (e.g., Langergraber et al 2007;Ryynänen et al 2007). Therefore, our study as well as other published studies confirmed a necessity of using a standardized measure of genetic differentiation when measures are based on different genetic markers.…”
Section: Discussionsupporting
confidence: 81%
“…They are independent of the amount of genetic variation and therefore suitable for comparisons between studies that employ different genetic markers. Although these measures are relatively new, they were already used in a few recently published studies that, together with our study, validated their use (e.g., Criscione et al 2007;Kettle et al 2007;Langergraber et al 2007;Ryynänen et al 2007;Leinonen et al 2008). Standardized F ST was usually several times higher than unstandardized F ST for microsatellite loci (e.g., Criscione et al 2007;Jordan and Snell 2008;González-Pérez et al 2009).…”
Section: Discussionsupporting
confidence: 69%
“…SNP markers, adaptive variation, and balancing selection SNPs offer the advantages of abundance, a simpler and better understood mutational mechanism than microsatellites, and relatively low rates of genotyping error, and because they are more often gene-linked, they will be particularly useful for studies of adaptive variation and selection processes (Ryyanen et al 2007). The confluence of massively parallel sequencing technologies and whole-genome or transcriptome sequences has given rise to the field of population genomics, where genome-wide scans of populations are undertaken to find genes underlying adaptive differentiation (GonzalezMartinez et al 2006;Luikart et al 2003).…”
Section: Molecular Marker Resourcesmentioning
confidence: 99%
“…Such sites occur in very high numbers in genomes of higher organisms. Recently, they have been regarded as the new genetic marker of choice, due to high frequencies, simple mutation mechanism and low error rates (Ryynanen et al 2007). Information concerning the utility of SNPs for population genetic and evolutionary studies in nonmodel organisms is scarce, in particular in genome scans (but see Rengmark et al 2006).…”
Section: Introductionmentioning
confidence: 99%